2021
DOI: 10.1007/s00704-021-03791-x
|View full text |Cite
|
Sign up to set email alerts
|

The significance of monitoring high mountain environments to detect heavy precipitation hotspots: a case study in Gredos, Central Spain

Abstract: In 2015, a new automatic weather station (AWS) was installed in a high elevation site in Gredos mountains (Central System, Spain). Since then, a surprisingly high number of heavy precipitation events have been recorded (55 days with precipitation over 50 mm, and a maximum daily precipitation of 446.9 mm), making this site a hotspot in Spain in terms of annual precipitation (2177 mm year) and extreme precipitation events. The neighboring stations available in the region with longer data series, including the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(65 reference statements)
1
2
0
Order By: Relevance
“…Convective precipitation demonstrates a bimodal distribution in mainland Portugal [22], with a peak in April and another in October, which is also consistent with the seasonal cycle of hailfall and lightning [23,24]. Sub-hourly heavy precipitation events in other parts of the Iberian Peninsula, namely, its western half, have also been related to similar largescale circulation patterns (westerly/south-westerly flow), with analogous seasonality [25]. However, these events in eastern Spain [26] are usually driven by different weather systems, originating and developing in the Mediterranean Sea (with a clear connection with sea surface temperatures) rather than in the North Atlantic, thus underlying the remarkable differences in their respective seasonal regimes.…”
Section: Introductionsupporting
confidence: 74%
“…Convective precipitation demonstrates a bimodal distribution in mainland Portugal [22], with a peak in April and another in October, which is also consistent with the seasonal cycle of hailfall and lightning [23,24]. Sub-hourly heavy precipitation events in other parts of the Iberian Peninsula, namely, its western half, have also been related to similar largescale circulation patterns (westerly/south-westerly flow), with analogous seasonality [25]. However, these events in eastern Spain [26] are usually driven by different weather systems, originating and developing in the Mediterranean Sea (with a clear connection with sea surface temperatures) rather than in the North Atlantic, thus underlying the remarkable differences in their respective seasonal regimes.…”
Section: Introductionsupporting
confidence: 74%
“…Accurate rainfall data are needed to understand the complexity of hydrological systems for water management and rainfall flood forecast, and to better understand extreme events, which can cause severe damage; these are scarcely documented and lead to difficulties in flood modeling [ 19 , 20 ]. Since precipitation (depth and intensity) is usually estimated by means of temporal averages and spatial interpolations that often do not represent their variability, accurate and reliable results can be achieved if good-quality hydrologic data are provided from a well-designed and well-implemented data collection program [ 11 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…(p. 12). Morán-Tejeda et al (2021) reported that the insights provided by a new weather station in the Sierra de Gredos, Spain, fundamentally altered understanding of the regional extreme precipitation climatology; such findings naturally call into question the informativeness and representativeness of the current network elsewhere. Zandler et al (2019) reported large differences between gridded precipitation products in the mountainous Pamir region of Tajikistan as a function of the number of contributing stations.…”
Section: Introductionmentioning
confidence: 99%